2020
DOI: 10.1212/wnl.0000000000008939
|View full text |Cite
|
Sign up to set email alerts
|

MRI vastus lateralis fat fraction predicts loss of ambulation in Duchenne muscular dystrophy

Abstract: ObjectiveWe studied the potential of quantitative MRI (qMRI) as a surrogate endpoint in Duchenne muscular dystrophy by assessing the additive predictive value of vastus lateralis (VL) fat fraction (FF) to age on loss of ambulation (LoA).MethodsVL FFs were determined on longitudinal Dixon MRI scans from 2 natural history studies in Leiden University Medical Center (LUMC) and Cincinnati Children's Hospital Medical Center (CCHMC). CCHMC included ambulant patients, while LUMC included a mixed ambulant and nonambul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 39 publications
13
69
0
1
Order By: Relevance
“…All scans except one were free from visible motion artefacts, indicating that all subjects could adhere to the protocol. The mean bias in FF between the segmentations of two independent observers was low (0.3%) and the limits of agreement were within ±3% in FF, which is in the same range as previously reported values in segmentation of the vastus lateralis in patients with Duchenne muscular dystrophy (bias: 0.1%, limits of agreement: ±1.1%), 28 in healthy controls and patients with type 2 diabetes in all leg muscle compartments (bias: −0.2, limits of agreement:…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All scans except one were free from visible motion artefacts, indicating that all subjects could adhere to the protocol. The mean bias in FF between the segmentations of two independent observers was low (0.3%) and the limits of agreement were within ±3% in FF, which is in the same range as previously reported values in segmentation of the vastus lateralis in patients with Duchenne muscular dystrophy (bias: 0.1%, limits of agreement: ±1.1%), 28 in healthy controls and patients with type 2 diabetes in all leg muscle compartments (bias: −0.2, limits of agreement:…”
Section: Discussionsupporting
confidence: 88%
“…All scans except one were free from visible motion artefacts, indicating that all subjects could adhere to the protocol. The mean bias in FF between the segmentations of two independent observers was low (0.3%) and the limits of agreement were within ±3% in FF, which is in the same range as previously reported values in segmentation of the vastus lateralis in patients with Duchenne muscular dystrophy (bias: 0.1%, limits of agreement: ±1.1%), 28 in healthy controls and patients with type 2 diabetes in all leg muscle compartments (bias: −0.2, limits of agreement: ±2.6%), 29 and in patients with myotonic dystrophy type 1 in lower leg muscles (limits of agreement: ±2.5%) 30 . The scan‐to‐scan reproducibility between the two Dixon scans with different resolutions showed a low average bias in FF (−0.7%) and narrow limits of agreement (−3.4% to 1.8%), which is lower than the difference found between the patients and the healthy controls (ie, ~4%), indicating the feasibility of assessing FFs using this method to detect affected muscles.…”
Section: Discussionsupporting
confidence: 88%
“…4 Particularly, fat-fraction mapping methods allow to quantitatively monitor the replacement of muscle by fat, the common final pathway in most NMDs, thus providing an objective marker of disease progression. 5,6 However, precise measures allowing monitoring the different pathophysiological processes and the histopathological alterations involved in the degenerative process would significantly improve the assessment of the effects and efficacy of therapies. 7 The water T 2 -relaxation in skeletal muscle has been shown to be sensitive, although not specific, to several pathological and even physiological processes affecting the water distribution and protein hydration in tissue, such as exercise, injury, interstitial edema, inflammation, necrosis, cell swelling, and acidification.…”
mentioning
confidence: 99%
“…In this context, quantitative magnetic resonance imaging (MRI) has been playing an important role in clinical trials 4 . Particularly, fat‐fraction mapping methods allow to quantitatively monitor the replacement of muscle by fat, the common final pathway in most NMDs, thus providing an objective marker of disease progression 5,6 . However, precise measures allowing monitoring the different pathophysiological processes and the histopathological alterations involved in the degenerative process would significantly improve the assessment of the effects and efficacy of therapies 7 …”
mentioning
confidence: 99%
“…23,24 A large number of studies showed a good to very good correlation of MFF with strength and function measures cross-sectionally in a wide range of muscle diseases, 12,19,[25][26][27][28] and recently MFF was even shown to be able to predict future function in Duchenne muscular dystrophy (DMD). 29,30 This represents an important step forward in the road to a surrogate end point in clinical trials. 13,31 A second approach for the reliable assessment of degenerative disease activity in muscle tissue including fatty degeneration represents T2 mapping of skeletal muscle.…”
mentioning
confidence: 99%